RcsAB and Fur Coregulate the Iron-Acquisition System via entC in Klebsiella pneumoniae NTUH-K2044 in Response to Iron Availability - Yuan, Lingyue; Li, Xuan; Du, Ling; Su, Kewen; Zhang, Jiaxue; Liu, Pin; He, Qiang; Zhang, Zhongshuang; Peng, Dan; Shen, Lifei; Qiu, Jingfu; Li, Yingli (Frontiers in Cellular and Infection Microbiology, 2020)
The iron acquisition system is an essential virulence factor for human infection and is under tight regulatory control in a variety of pathogens. Ferric-uptake regulator (Fur) is one of Fe2+-responsive transcription factor that maintains iron homeostasis, and the regulator of capsule synthesis (Rcs) is known to regulate exopolysaccharide biosynthesis. We speculate the Rcs may involve in iron-acquisition given the identified regulator box in the upstream of entC that participated in the biosynthesis of enterobactin. To study the coregulation by RcsAB and Fur of entC, we measured the β-galactosidase activity and relative mRNA expression of entC in WT and mutant strains. The RcsAB- and Fur-protected regions were identified by an electrophoretic mobility shift assay (EMSA) and a DNase Ι footprinting assay. A regulatory cascade was identified with which Fur repressd rcsA expression and reduced RcsAB and entC expression. Our study demonstrated that entC was coregulated by two different transcriptional regulators, namely, RcsAB and Fur, in response to iron availability in Klebsiella pneumoniae.